Towards consensus on land use impacts on biodiversity in LCA: UNEP/SETAC Life Cycle Initiative preliminary recommendations based on expert contributions. (20th January 2016) - Teixeira, Ricardo F.M.; Maia de Souza, Danielle; Curran, Michael P.; Antón, Assumpció; Michelsen, Ottar; Milà i Canals, Llorenç
Abstract: The United Nations Environment Programme/Society of Environmental Toxicology and Chemistry (UNEP/SETAC) Life Cycle Initiative organized two consensus-building workshops regarding Life Cycle Assessment (LCA) models and indicators for land use impacts on biodiversity. This article presents a synthesis of the main recommendations drawn from the opinions of the experts present, from the Initiative's perspective. The needs of LCA practitioners are crucial to determine what characteristics biodiversity assessment models should possess. Available models are mainly apt for impact hotspot detection in supply chains. If the goal is to assess the impacts of plot-level management practices they should be accompanied by other more detailed tools beyond LCA. Site-specific data are necessary to accurately assess biodiversity loss at regional and local scale, despite known constraints imposed by life cycle inventories. Examples of datasets are provided in this article. Species richness is a promising start for these models but it must be complemented with metrics for habitat configuration and intensity-based indicators. Finally, modelling results should be better coupled with policy decisions and existing strategic plans. Graphical abstract: Highlights: 14/24 experts met in San Francisco/Brussels to discuss biodiversity loss in LCA. Biodiversity should be quantified by LCA using an explicit modelling framework. Using species richness is a good starting point to model biodiversity loss. Good indicators possess regional state and pressure components. Models and indicators should fit the purpose of the study.